INFLUENCE OF MANAGERIAL OWNERSHIP AND INSTITUTIONAL OWNERSHIP OF FINANCIAL PERFORMANCE IN LISTED PULP AND PAPER COMPANIES IN INDONESIA EXCHANGE - Hadriana Hanafie (Universitas Patria Artha, 2019)
The objectives of this study are: 1) to find out and analyze the effect of managerial ownership on financial performance on Pulp and Paper companies listed on the Indonesia Stock Exchange, and 2) to determine and analyze the effect of institutional ownership on financial performance on Pulp and Paper companies listed on Indonesia stock exchange. Data collection was carried out through documentation techniques in the form of financial statements for 5 years from 2013 to 2017 with the type of data pooling research. Pulp and Paper company research subjects listed on the Indonesia Stock Exchange. The data analysis technique used in this study is the multiple regression equation. The results showed that 1) the results of the study indicated that the application of managerial ownership in the sample company had been effective so that it had an influence in helping the unification of interests between managers and owners that could motivate managers to take action to improve the company's financial performance and 2) the results of this study proved that investors the institution is unable to professionally monitor the development of its investment in a company, thus the level of control over actions and management performance is very lacking so that the potential for fraud that can harm the company cannot be suppressed